Gallic Acid Alleviates Acetaminophen-Induced Acute Liver Injury by Regulating Inflammatory and Oxidative Stress Signaling Proteins - Jing Zhao; Yuan Zhao; Shuzhe Song; Sai Zhang; Guodong Yang; Yan Qiu; Weishun Tian (Antioxidants)
Acetaminophen (APAP) overdose is a major cause of drug-induced liver injury (DILI) globally, which necessitates effective therapies. Gallic acid (GA), a naturally abundant polyphenol, possesses potent antioxidant and anti-inflammatory properties that may overcome the limitations of N-acetylcysteine (NAC), such as its narrow therapeutic window. This study systematically investigated the hepatoprotective effects and underlying molecular mechanisms of GA against APAP-induced acute liver injury (ALI). Mice received an intraperitoneal injection of APAP (300 mg/kg), followed by an oral administration of GA (50 or 100 mg/kg) or NAC (150 mg/kg) 1 h post-intoxication. Both GA and NAC significantly ameliorated hypertrophy and histopathological damage, as evidenced by reduced serum ALT/AST levels and inflammatory cytokines. TUNEL staining revealed a marked suppression of apoptotic and necrotic cell death, further supported by the downregulation of pro-apoptotic Bax and the upregulation of anti-apoptotic Bcl-2 mRNA expression. GA and NAC treatment restored hepatic glutathione (GSH) content, enhanced antioxidant enzyme gene expression, and reduced malondialdehyde (MDA) accumulation. Mechanistically, GA and NAC inhibited MAPK phosphorylation while activating AMPK signaling. Taken together, these findings demonstrate that GA mitigates APAP-induced ALI by modulating oxidative stress and inflammation through the regulation of MAPK/AMPK signaling proteins.